Test of the Potential of Ethanol Extracts, Simplician Medium and Forest Umbi Juice (Eleutherine bulbosa (Factory) Urb.) against Blood Glucose Levels of Rats, and Histopatology Ratkreas Rat (Rattus norvegicus) Hypercolesterolemia Model Diabetic - Joni Tandi; Tien Wahyu Handayani; Ni Wayan Ika Purwasih (Journal of Tropical Pharmacy and Chemistry, 2020)
This study aims to examine the presence or absence of secondary metabolite compounds in ethanol extract, simplicia steeping and forest onion tuber juice, in male glucose parameters and pancreatic histopathology. Using test animals as many as 30 male white rats divided into 6 groups and each group consisted of 5 rats with group I details as normal controls, group II as negative controls given 0.5% Na-CMC suspension, group III as positive control who were given Metformin 45 mg / kg BB and IV, V, VI as the test group were given ethanol extract, simplicia extract and forest onion tuber juice with each dose of 20 g / kg BW. The results showed that there were secondary metabolites in the ethanol extract of forest onion tubers, namely flavonoids, saponins, alkaloids, steroids and tannins, giving ethanol extract of forest onion bulbs had the effect of reducing blood glucose levels in white mice with a dose of 20g / kgBW with an average of 132 and ethanol extract of forest onion bulbs at a dose of 20g / kg BB with an average of 0.5 can regenerate pancreatic tissue.